SCIENTIFIC CONTRIBUTION AND SIGNIFICANCE OF LIFELONG WORK OF PROFESSOR DR. ANDON KOSTADINOVIC - Djordjević, Radomir D (Journal of process management and new technologies, 2019)
BIOGAPHY OF EMERITUS PROFESSOR DR. ANDON G. KOSTADINOVIC